Conductive ink based on high-entropy alloy aerogel as well as preparation method and application of conductive ink
By preparing three-dimensional nanoporous high-entropy alloy aerogel conductive ink, the shortcomings of existing conductive inks in terms of conductivity, cost and oxidation resistance are solved, achieving low-temperature sintering and high flexibility, which is suitable for high-precision processing of flexible electronic devices.
Patent Information
- Application Number
- CN202610429843.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-02
- Publication Date
- 2026-05-15
AI Technical Summary
Existing carbon-based and metal-based conductive inks have shortcomings in terms of conductivity, cost, oxidation resistance, and sintering temperature, making it difficult to meet the high-precision and low-temperature processing requirements of flexible electronic devices.
High-entropy alloy aerogel with a three-dimensional nanoporous structure is used as a conductive filler. Conductive ink is prepared by sol-gel method and low-temperature sintering technology. The high conductivity, oxidation resistance and thermal stability of high-entropy alloy are utilized to form a dense conductive network.
It achieves high conductivity, low temperature sintering and excellent mechanical flexibility, making it suitable for flexible electronic devices and laser direct writing technology, reducing processing costs and process complexity.
Smart Images

Figure CN122037665A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of functional materials and printed electronics, specifically to a conductive ink based on high-entropy alloy aerogel, its preparation method, and its application. Background Technology
[0002] With the rapid development of flexible electronics, smart sensors, and printed electronics, the performance requirements for conductive inks are constantly increasing. As an important material for constructing flexible circuits and electronic devices, conductive inks must possess high conductivity, excellent stability, good flexibility, and ease of processing to meet the needs of use in complex environments.
[0003] However, conductive inks currently on the market are mainly divided into two categories: carbon-based materials and metal-based materials. Both types of materials have certain limitations in practical applications. The first type is carbon-based conductive ink, with common materials including graphene and carbon nanotubes. These materials have good chemical stability, flexibility, and low cost; however, their conductivity is relatively low, failing to meet the requirements of high-precision and high-performance circuits. Furthermore, graphene and carbon nanotubes have poor dispersion, making uniform coating difficult, and large-scale production processes are complex and cost control is challenging. The other type is metal-based conductive ink, with common materials including silver nanoparticles and copper nanoparticles. These materials have excellent conductivity and are currently the most widely used conductive inks. However, silver-based inks are expensive, limiting their large-scale application; copper-based inks, although lower in cost, are easily oxidized in air, leading to a decrease in conductivity; metal nanoparticle inks typically require high sintering temperatures (>300℃) to achieve a dense conductive network, limiting their application on flexible substrates. Therefore, developing new high-performance conductive inks to overcome the shortcomings of existing technologies and meet the demands for high conductivity, low cost, and low-temperature processability has become a research hotspot.
[0004] In recent years, high-entropy alloys (HEAs), as a novel multi-component alloy material, have gradually attracted widespread attention due to their unique composition design and excellent performance. Unlike traditional alloys, HEAs are typically composed of five or more elements in equal proportions, exhibiting the following significant characteristics: high conductivity and high stability: HEAs have a uniform element distribution, possessing good electrical conductivity and oxidation resistance, making them suitable for high-precision electronic devices; thermodynamic stability: the high-entropy effect endows them with excellent thermodynamic stability, maintaining a stable structure even at high temperatures; and designability: through reasonable element ratios, the electrical, mechanical, and chemical properties of HEAs can be precisely controlled to meet the needs of different application scenarios. However, developing HEAs into conductive inks and applying them in flexible electronic devices and laser direct writing technology still faces the following key challenges: the optimal parameters for the preparation process of HEAs nanoparticles are unclear, the ink dispersion stability is insufficient, there are bottlenecks in the application of low-temperature sintering technology, and the processing technology needs further optimization.
[0005] Therefore, providing a conductive ink based on a high-entropy alloy and its preparation method is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] To address the aforementioned problems, this invention provides a conductive ink based on high-entropy alloy aerogel, its preparation method, and its application. By introducing a high-entropy alloy aerogel conductive framework with a three-dimensional nanoporous structure, this invention achieves high conductivity, low-temperature sintering, and excellent mechanical flexibility in the conductive ink, solving the problems of insufficient conductivity, high sintering temperature, or poor oxidation resistance of existing carbon-based and metal-based conductive inks.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] A conductive ink based on high-entropy alloy aerogel, wherein the conductive filler is high-entropy alloy aerogel; The high-entropy alloy aerogel has a three-dimensional interconnected nanoporous structure with a specific surface area of 200-500 m². 2 / g, density less than 0.05g / cm³ 3 The average pore size is 10-200 nm.
[0009] The high-entropy alloy aerogel of this invention is prepared by sol-gel method and drying process. It has ultra-light weight, nanoscale pore structure and ultra-high specific surface area, which can effectively improve the dispersibility and conductivity of ink. In addition, in application, the aerogel structure can be rapidly formed at a low temperature by low-temperature sintering technology, which can further improve the performance and practicality of conductive ink.
[0010] Preferably, the high-entropy alloy aerogel is composed of at least five metal elements in an equimolar ratio, and the metal elements include at least five of the following: Al, Co, Cr, Fe, Ni, Ti, Mn, Cu, Zn, V, Mo, Sn, Ag, and Au. The high-entropy alloy aerogel has a mass fraction of 10-60% in the conductive ink.
[0011] Preferably, the preparation method of the high-entropy alloy aerogel includes the following steps: (1) Dissolve the metal precursor of the high entropy alloy in deionized water at an equimolar ratio to form a homogeneous precursor solution; then add a complexing agent to the precursor solution and obtain a gel through a sol-gel reaction; (2) The gel is freeze-dried or supercritical dried to obtain a high-entropy alloy aerogel with a three-dimensional nanoporous structure.
[0012] Preferably, the total concentration of the high-entropy alloy metal precursor in the precursor solution in step (1) is 0.05-1.0 mol / L, the complexing agent is selected from at least one of citric acid, tartaric acid, oxalic acid, ethylenediaminetetraacetic acid and their salts, and the amount of complexing agent added is 1-3 times the total mass of metal ions in the high-entropy alloy metal precursor; The freeze-drying temperature in step (2) is -60~-30℃ and the drying time is 24-72h; the supercritical drying adopts supercritical carbon dioxide drying, with a drying temperature of 30-60℃, a pressure of 7.5-20MPa, and a drying time of 1-8h, so as to preserve the nanoporous structure of the high-entropy alloy aerogel.
[0013] Preferably, the specific steps of the sol-gel reaction are as follows: a complexing agent is added to the precursor solution, and the mixture is stirred at 300-800 r / min for 1-4 h at 60-90℃ to form a stable complexed metal solution; under stirring conditions, ammonia water is added dropwise to adjust the pH value of the solution to 6-8, so that the solution gradually forms a uniform sol; then the prepared sol is transferred to a mold and allowed to stand for 1-24 h to allow the sol to gradually coagulate and form a gel.
[0014] Preferably, the sol-gel reaction temperature is about 80°C and the stirring speed is about 500 r / min.
[0015] Preferably, the conductive ink further includes a solvent, a dispersant, and a binder, wherein the high-entropy alloy aerogel has a mass fraction of 10-60% in the conductive ink, the solvent has a mass fraction of 20-80%, the dispersant has a mass fraction of 0.1-5%, and the binder has a mass fraction of 1-20%.
[0016] Preferably, the solvent is at least one selected from ethanol, water, and ethylene glycol; The dispersant is at least one of polyvinylpyrrolidone or other nonionic surfactants; The adhesive is at least one of polyvinyl alcohol, hydroxypropyl methylcellulose, and acrylic resin.
[0017] Preferably, the conductive ink further includes any one of a stabilizer, a wetting agent, and a surfactant.
[0018] Preferably, the physical parameters of the conductive ink are: viscosity of 10-100 mPa·s, average particle size of less than 500 nm, storage stability of not less than 30 days, and suitable for inkjet printing, screen printing and laser direct writing processes.
[0019] The method for preparing conductive ink based on high-entropy alloy aerogel as described above specifically includes the following steps: High-entropy alloy aerogel is dispersed in a solvent, and a dispersant and binder are added for mechanical stirring and ultrasonic dispersion. By adjusting the amount of solvent and / or the solid content of the high-entropy alloy aerogel powder (adding diluent or thickener if necessary), the viscosity of the resulting conductive ink at 25°C is made to be 10-100 mPa·s, thus obtaining a uniform and stable conductive ink.
[0020] The application of conductive inks based on high-entropy alloy aerogels as described above, or conductive inks based on high-entropy alloy aerogels prepared by the methods described above, in the preparation of conductive patterns.
[0021] Preferably, the specific steps of the method for preparing the conductive pattern are as follows: After the conductive ink is applied to the substrate surface to form a predetermined pattern, it is then sintered at 150-300℃ for 5-60 minutes to cause the high-entropy alloy aerogel skeleton to fuse and densify, forming a continuous conductive network.
[0022] Preferably, the conductive ink is applied to the surface of a flexible or rigid substrate by means of laser direct writing, inkjet printing or screen printing.
[0023] Preferably, the conductive layer formed after sintering has a thickness of 1-10 μm, a resistivity of less than 10 Ω / cm, a surface roughness of less than 50 nm, and maintains its conductivity at 200°C in air without significant degradation. After being repeatedly bent 1000 times on a flexible PI or PET substrate, the resistance change rate of the conductive pattern is less than 10%, demonstrating excellent mechanical stability and flexibility.
[0024] Preferably, the conductive pattern is used in flexible electronic devices, strain sensors, temperature sensors, or printed electronic circuits.
[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) Material system innovation: This invention is the first to construct a multi-component high-entropy alloy into an aerogel form and use it as a conductive skeleton for conductive ink, which has high conductivity, oxidation resistance and thermal stability. (2) Low-temperature sintering capability: By utilizing the high specific surface area and three-dimensional interconnected channels of high-entropy alloy aerogel, the conductive network can be rapidly formed at 150-300℃, which greatly reduces the sintering temperature and is applicable to flexible polymer substrates. (3) Excellent mechanical flexibility: The aerogel skeleton of the present invention can buffer the strain concentration during bending, so that the conductive layer still maintains a small resistance change after more than 1,000 bending cycles. (4) Strong compatibility with processes and applications: The rheological properties of the conductive ink of this invention are adjustable, and it can be adapted to various processing methods such as laser direct writing, inkjet printing and screen printing. It can be widely used in flexible electronic devices, strain / temperature sensors and large-area printed electronic circuits. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. The drawings in this description are merely embodiments of the present invention.
[0027] Figure 1 This is a process flow diagram of an embodiment of the present invention for the application of conductive ink based on high-entropy alloy aerogel; Figure 2 The images show the TEM and EDS results of the high-entropy alloy aerogel prepared in Example 1 of the present invention, where (a) is the TEM characterization image of the high-entropy alloy aerogel, and (b)-(f) are the EDS results of Bi, Fe, Al, Co and Ni metal elements in the high-entropy alloy aerogel. Figure 3 This is a TEM image of the high-entropy alloy aerogel prepared in Example 1 of the present invention; Figure 4 The diagram and result diagram of the bending test of the conductive ink direct writing conductive circuit in Embodiment 2 of the present invention are shown, wherein (a) is a schematic diagram and (b) is a result diagram; Figure 5 This is a diagram showing the high heat preservation result of the block resistor in Embodiment 3 of the present invention. Detailed Implementation
[0028] Embodiments of the present invention are described below, examples of which are shown in the accompanying drawings. The embodiments described with reference to the drawings are exemplary and intended to explain the present invention, but are not to be construed as limiting the present invention.
[0029] Example 1 like Figure 1 This invention provides a method for preparing conductive ink based on high-entropy alloy aerogel, specifically including the following steps: (1) Preparation of high-entropy alloy aerogels: Metal precursors Al(NO3)3·9H2O, Co(NO3)2·6H2O, BiCl3, Fe(NO3)3·9H2O, and NiCl2 were dissolved in deionized water in a metal element molar ratio of 1:1:1:1:1:1, controlling the total concentration of metal ions in the solution to be 0.1 mol / L. The solution was stirred until homogeneous to form a uniform precursor solution. Then, a complexing agent (mass twice the total mass of metal ions) was added to the precursor solution, and the solution was stirred at 60℃ and 500 r / min for 2 h to form a stable complexed metal solution. Under stirring conditions, ammonia water (1 mol / L) was added dropwise to adjust the pH value to about 7.0, allowing the solution to gradually form a uniform sol. The prepared sol was transferred to a polytetrafluoroethylene mold and allowed to stand for 24 h to allow the sol to gradually coagulate and form a gel. The formed gel was placed in a freeze dryer and freeze-dried at -50 to -60°C for 48 hours to remove moisture while retaining the porous nanostructure of the gel, thus obtaining a high-entropy alloy aerogel. The aerogel was characterized by BET surface area measurement and mercury intrusion porosimetry pore size analysis. The specific surface area of the high-entropy alloy aerogel was approximately 280 m² / s. 2 / g, apparent density is approximately 0.03g / cm³ 3 The average pore size is about 50 nm, indicating that the aerogel has a typical lightweight porous structure. Figure 2 The TEM and EDS test results of the high-entropy alloy aerogel show that the composition of the high-entropy alloy aerogel is uniform. Figure 3 The TEM test results of the high-entropy alloy aerogel show that a two-dimensional interconnected metal network structure is formed in the aerogel, creating nanoscale interconnected channels. (2) The high-entropy alloy aerogel powder obtained in step (1) was added to a mixed solvent of ethanol and ethylene glycol. The mass ratio of aerogel powder to mixed solvent was 1:5, and the mass ratio of ethanol to ethylene glycol was 1:4. Ethanol was mainly used to reduce the viscosity of the system and provide a faster evaporation rate, while ethylene glycol was used to improve the wettability of the solution and the continuity of film formation. This ratio showed good adaptability to spraying / direct writing and film formation quality in the preliminary experiment. Then, 1 wt% of polyvinylpyrrolidone (PVP) was added to improve the dispersion stability of aerogel particles in the solvent and prevent agglomeration. Adding 2 wt% polyvinyl alcohol (PVA) enhances the coating performance and adhesion of the conductive ink. Finally, the ink is treated with an ultrasonic disperser for 1 hour (frequency 40 kHz) to ensure that the high-entropy alloy aerogel particles are uniformly dispersed in the solvent, resulting in a stable conductive ink system. Subsequently, the viscosity of the conductive ink is measured by a rotational viscometer. The solid content of the ink is adjusted by appropriately increasing or decreasing the amount of mixed solvent, so that the viscosity of the ink at 25°C in this embodiment is about 40 mPa·s, which is within the applicable range of 10-100 mPa·s recommended by this invention.
[0030] Example 2 like Figure 1 This invention provides an application of conductive ink based on high-entropy alloy aerogel in laser direct writing circuits, specifically including the following steps: (1) Laser direct writing technology for processing conductive patterns The conductive ink prepared in Example 1 was loaded into a laser direct writing system and laser direct writing was performed on a flexible PET film substrate. The laser parameters were set as follows: laser wavelength 1064nm, laser power 2W, and scanning speed 10-50mm / s. Under the action of laser energy, the conductive ink was rapidly cured to form an initial conductive pattern. Subsequently, the processed sample was placed in an oven at 150℃ for low-temperature sintering for 30min, which further fused the high-entropy alloy aerogel skeleton in the conductive layer to form a continuous and dense conductive network. The thickness of the conductive line after sintering was measured to be approximately 3μm and the line width was approximately 100μm, with uniform thickness distribution along the line width direction. Conductivity test: The resistance value of the laser-written conductive circuit was measured using the four-probe test method. The results showed that the resistance value of the conductive circuit was 10Ω / cm, indicating that the conductivity performance was excellent and stable. Laser direct-write circuit bending performance test: The bending test was conducted in accordance with the group standard T / ZACA 040-2022 "Test Method for Bending Performance of Flexible Display Modules". A two-dimensional moving platform and a self-designed bending fixture were used to conduct a cyclic bending test on the direct-write structure. The results are shown in […]. Figure 4 ,in Figure 4(a) is a test schematic diagram, in which the conductive circuit has been directly written on the PI film. (b) is the bending test result. As can be seen from the figure, after the conductive pattern of the conductive ink is repeatedly bent 1000 times, the resistance value changes by less than 10%, which shows excellent mechanical stability.
[0031] Example 3 This embodiment provides a method for preparing conductive ink based on high-entropy alloy aerogel and its application. This embodiment is basically the same as Embodiments 1 and 2, except that the combination of high-entropy alloy metal elements, the type of complexing agent, and some process parameters are as follows. (1) Preparation of high-entropy alloy aerogels: Aluminum nitrate, cobalt nitrate, chromium nitrate, iron nitrate, and nickel nitrate were selected as metal precursors and dissolved in deionized water at an equimolar ratio of Al:Co:Cr:Fe:Ni = 1:1:1:1:1 to obtain a total metal ion concentration of 0.1 mol / L, thus obtaining a precursor solution. Sodium citrate was added to the precursor solution as a complexing agent, with the amount of sodium citrate added being twice the total mass of the metal ions. The mixture was stirred at 70℃ and 500 r / min for 2 h to form a stable complexed metal solution. Ammonia was added dropwise under stirring to adjust the pH of the solution to 7.0, gradually forming a homogeneous sol. The resulting sol was poured into a mold and allowed to stand for 12 h to complete the gelation process. The formed gel was placed in a freeze dryer and dried. 50~ The aerogel was dried at 40℃ for 48 hours to remove moisture, resulting in a high-entropy alloy aerogel with a porous nanostructure. BET analysis showed that the specific surface area of the aerogel was approximately 260 m². 2 / g, apparent density is approximately 0.032g / cm³. 3 ; (2) Preparation of conductive ink: The high-entropy alloy aerogel powder obtained in step (1) was added to a mixed solvent of ethanol / ethylene glycol / water (mass ratio 1:3:1). The mass ratio of aerogel powder to mixed solvent was 1:5. In this embodiment, the mass of aerogel powder was 5g and the total mass of mixed solvent was 25g. 1wt% PVP was added as a dispersant and 3wt% PVA was added as a binder. The mixture was mechanically stirred for 30min and then ultrasonically dispersed for 1h to obtain a uniform slurry. The solid content was adjusted by adding appropriate amounts of mixed solvent so that the viscosity of the ink at 25℃ was about 60mPa·s. (3) Preparation and performance testing of conductive patterns The conductive ink was screen-printed onto a PI flexible substrate with a line width of approximately 150 μm; then, it was heat-treated at 200°C for 20 min to complete low-temperature sintering; the thickness of the conductive line was measured to be approximately 4 μm using a profilometer. The sheet resistance measured using the four-probe method was approximately 8 Ω / cm; after 1000 reciprocating bends with a bending radius of 5 mm, the change rate of sheet resistance was less than 8%; after holding at 200℃ and 300℃ for 72 h respectively, the results were as follows. Figure 5 As shown, the sheet resistance change rate is less than 10%; This embodiment demonstrates that, within the scope of this invention, by changing the combination of high-entropy alloying elements and the solvent ratio, a conductive pattern with low resistance and good flexibility can still be obtained.
[0032] Example 4 This embodiment provides a method for preparing and applying a high-entropy alloy aerogel conductive ink suitable for inkjet printing. This embodiment is basically the same as Embodiment 1, except that different solvent systems and process parameters are used to obtain a low-viscosity ink suitable for inkjet printing. (1) Preparation of high-entropy alloy aerogels: Cobalt nitrate, chromium nitrate, ferric nitrate, manganese nitrate, and nickel nitrate were used as metal precursors and dissolved in deionized water at a molar ratio of Co:Cr:Fe:Mn:Ni = 1:1:1:1:1, with a total metal ion concentration of 0.2 mol / L. Tartaric acid was added as a complexing agent at an amount 2.5 times the total mass of the metal ions. The mixture was stirred at 60℃ and 400 r / min for 3 h, and then ammonia was added dropwise to adjust the pH to 6.5 to obtain a homogeneous sol. The sol was poured into a mold and allowed to stand for 8 h to allow it to gradually coagulate and form a gel. The obtained gel was first placed in The aerogel was frozen at 40℃ for 36 hours to fix its three-dimensional network structure, and then transferred to a supercritical carbon dioxide drying apparatus to remove the solvent from the pores under drying conditions of 40℃, 12MPa, and 3 hours, yielding a high-entropy alloy aerogel. BET analysis showed that the specific surface area was approximately 300 m² / g. 2 / g, apparent density approximately 0.028g / cm³ 3 ; (2) Preparation of conductive ink: The 3g high-entropy alloy aerogel powder obtained in step (1) was dispersed in a water / ethanol mixed solvent. The mass ratio of aerogel powder to mixed solvent was 1:8. In this embodiment, the total mass of mixed solvent was 24g, and the mass ratio of water to ethanol was 3:2. 0.5wt% PVP was added as a dispersant and 2wt% acrylic resin emulsion was added as a binder. The mixture was magnetically stirred for 40min and ultrasonically dispersed for 30min to obtain uniform ink. By adding a small amount of aqueous solvent to adjust the solid content, the viscosity of the ink at 25℃ was about 20mPa·s, and the surface tension was controlled at 30-35mN / m, which met the requirements of inkjet printing for rheological properties. (3) Inkjet printing and performance: The conductive ink was loaded into an inkjet printhead and a serpentine conductive pattern was printed on a PET film substrate. The nozzle diameter was 30 μm and the printing resolution was 600 dpi. After printing, the printhead was heat-treated at 180°C for 15 min. The thickness of the conductive line was measured to be approximately 2 μm and the line width to be approximately 80 μm. The four-probe test results showed that the sheet resistance was about 15Ω / cm, and the sheet resistance change rate was less than 10% after 500 bends at a bending radius of 5mm.
[0033] This embodiment illustrates that, within the solvent ratio, dispersant, and binder ranges defined in this invention, a high-entropy alloy aerogel conductive ink suitable for inkjet printing can be obtained by adjusting the solid content and heat treatment conditions.
[0034] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A conductive ink based on high-entropy alloy aerogel, characterized in that, The conductive filler is a high-entropy alloy aerogel; The high-entropy alloy aerogel has a three-dimensional interconnected nanoporous structure with a specific surface area of 200-500 m². 2 / g, density less than 0.05g / cm³ 3 The average pore size is 10-200 nm.
2. The conductive ink based on high-entropy alloy aerogel according to claim 1, characterized in that, The high-entropy alloy aerogel is composed of at least five metal elements in an equimolar ratio, and the metal elements include at least five of the following: Al, Co, Cr, Fe, Ni, Ti, Mn, Cu, Zn, V, Mo, Sn, Ag, and Au. The high-entropy alloy aerogel has a mass fraction of 10-60% in the conductive ink.
3. The conductive ink based on high-entropy alloy aerogel according to claim 1, characterized in that, The preparation method of the high-entropy alloy aerogel includes the following steps: (1) Dissolve the high-entropy alloy metal precursor in deionized water at an equimolar ratio to obtain a homogeneous precursor solution; then add a complexing agent to the precursor solution to induce a sol-gel reaction and obtain a gel. (2) The gel is freeze-dried or supercritical dried to obtain a high-entropy alloy aerogel with a three-dimensional nanoporous structure.
4. The conductive ink based on high-entropy alloy aerogel according to claim 3, characterized in that, In step (1), the total concentration of the high-entropy alloy metal precursor in the precursor solution is 0.05-1.0 mol / L, the complexing agent is selected from at least one of citric acid, tartaric acid, oxalic acid, ethylenediaminetetraacetic acid and their salts, and the amount of complexing agent added is 1-3 times the total mass of metal ions in the high-entropy alloy metal precursor. The freeze-drying temperature in step (2) is -60~-30℃, and the drying time is 24-72h; the supercritical drying adopts supercritical carbon dioxide drying, with a drying temperature of 30-60℃, a pressure of 7.5-20MPa, and a drying time of 1-8h.
5. The conductive ink based on high-entropy alloy aerogel according to claim 1, characterized in that, The conductive ink further includes a solvent, a dispersant, and a binder, wherein the high-entropy alloy aerogel has a mass fraction of 10-60% in the conductive ink, the solvent has a mass fraction of 20-80%, the dispersant has a mass fraction of 0.1-5%, and the binder has a mass fraction of 1-20%.
6. The conductive ink based on high-entropy alloy aerogel according to claim 5, characterized in that, The solvent is at least one of ethanol, water, and ethylene glycol; The dispersant is at least one of polyvinylpyrrolidone or other nonionic surfactants; The adhesive is at least one of polyvinyl alcohol, hydroxypropyl methylcellulose, and acrylic resin.
7. A method for preparing conductive ink based on high-entropy alloy aerogel as described in any one of claims 1-6, characterized in that, Includes the following steps: High-entropy alloy aerogel is dispersed in a solvent, and a dispersant and binder are added for mechanical stirring and ultrasonic dispersion. By adjusting the amount of solvent and / or the solid content of the high-entropy alloy aerogel powder, the viscosity of the resulting conductive ink at 25°C is made to be 10-100 mPa·s, thus obtaining a uniform and stable conductive ink.
8. The application of the conductive ink based on high-entropy alloy aerogel as described in any one of claims 1-6, or the conductive ink based on high-entropy alloy aerogel obtained by the preparation method of claim 7, in the preparation of conductive patterns.
9. The application according to claim 8, characterized in that, The specific steps of the method for preparing the conductive pattern are as follows: The conductive ink is applied to the substrate surface to form a predetermined pattern, and then sintered at 150-300℃ for 5-60 minutes to form a continuous conductive network.
10. The application according to claim 8, characterized in that, The conductive pattern is used in flexible electronic devices, strain sensors, temperature sensors, or printed electronic circuits.